2022
DOI: 10.1097/mcg.0000000000001813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Intelligence With Other Interventions to Improve Adenoma Detection Rate for Colonoscopy

Abstract: Introduction: Recent randomized controlled trials (RCTs) and metaanalysis have demonstrated improved adenoma detection rate (ADR) for colonoscopy with artificial intelligence (AI) compared with highdefinition (HD) colonoscopy without AI. We aimed to perform a systematic review and network meta-analysis of all RCTs to assess the impact of AI compared with other endoscopic interventions aimed at increasing ADR such as distal attachment devices, dye-based/virtual chromoendoscopy, water-based techniques, and ballo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We speculate that the benefits will be higher in low detectors as Zhao et al 13 suggested a more pronounced effect. Fifth, with the advent of artificial intelligence (AI), assisted colonoscopy procedures and its effects on ADR, the effects of a longer WT in AI-assisted colonoscopy need to be evaluated 23,24 . Sixth, long-term follow-up is required to delineate the effects of 9WT on interval cancer rate incidence.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the benefits will be higher in low detectors as Zhao et al 13 suggested a more pronounced effect. Fifth, with the advent of artificial intelligence (AI), assisted colonoscopy procedures and its effects on ADR, the effects of a longer WT in AI-assisted colonoscopy need to be evaluated 23,24 . Sixth, long-term follow-up is required to delineate the effects of 9WT on interval cancer rate incidence.…”
Section: Discussionmentioning
confidence: 99%
“…They all show a more or less significant increase in detection of small adenomas. The same results are summarized over and over again in no less than 16 meta-analyses 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 , plus a protocol for a further one 36 , as well as a meta-analysis of some of these meta-analyses 37 !…”
mentioning
confidence: 97%
“…They all show a more or less significant increase in detection of small adenomas. The same results are summarized over and over again in no less than 16 meta-analyses [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], plus a protocol for a further one [36], as well as a meta-analysis of some of these meta-analyses [37]! "The question relates to the ultimate clinical relevance of increasing ADR from high to even higher levels …, we still do not know whether we have a cutoff ADR level, above which there is no further improvement in cancer prevention.…”
mentioning
confidence: 97%
“…7 A network MA had reported that AI-assisted colonoscopy achieved higher ADR than the use of distal attachments. 8 There are currently no published data on the combined use of AI-assisted colonoscopy and distal attachments, which logically would be synergistic and should further increase ADR. However, there is an ongoing RCT (NCT05133544) on the use Endocuff with or without AI-assisted colonoscopy in the detection of colorectal adenoma.…”
mentioning
confidence: 99%
“…A recent RCT with 1813 subjects reported that Endocuff Vision significantly increased ADR (47.8% vs 40.8%; RR 1.17, 95% CI: 1.06–1.30) in a CRC screening program where patients underwent colonoscopy following a positive fecal immunochemical test 7 . A network MA had reported that AI‐assisted colonoscopy achieved higher ADR than the use of distal attachments 8 . There are currently no published data on the combined use of AI‐assisted colonoscopy and distal attachments, which logically would be synergistic and should further increase ADR.…”
mentioning
confidence: 99%